Nanomateriais na Reabilitação de Património Arquitetónico - Franco, Carlos Manuel (2017)
The present article aims to contribute to stimulate the introduction of nanostructured materials in rehabilitation interventions, with new characteristics and new properties, such as self-cleaning, invoking its advantages when applied to the coating of exposed surfaces particularly in aggressive environments. The buildings in the big cities are confronted with aggravated environmental problems, mainly due to its continuous exposure to the highly polluting gases emitted by the intense and continuous traffic and by the installed industry in the periphery, negatively reflecting on the quality of the air, with the consequent degradation of building facades, resulting in higher costs and greater need for maintenance works. The structural stabilization, with the use of composite materials, notably the application of carbon fibers, of substantially improved handling - for their lightness, flexibility and resistance, allowing a minimal intervention, less intrusive, will guarantee a faster execution, reducing the number of necessary workers/equipment in the dockyard.